Pollutant removal from dairy wastewater using live Azolla filiculoides in batch and continuous bioreactors. (14th June 2021) - Khodadad Hosseini, Ensieh; Derakhshi, Pirouz; Rabbani, Mohammad; Mooraki, Nargess
Abstract: Fast and proper treatment of dairy wastewater is necessary before discharging it to the environment. In this study, healthy Azolla filiculoides was used to remove pollutants, including phosphorus (P), sodium (Na), chemical oxygen demand (COD), biological oxygen demand (BOD), and total dissolved solids (TDS) of dairy effluent in batch, continuous system, as well as continuous with the slow stirring system. These systems were handmade. The maximum removal efficiency was related to the P, which obtained 66.25% after 12 h in the batch bioreactor system. The highest removal of 13.69% after 21 h was obtained for Na using continuous with a slow stirring method. The highest removal related to the COD and BOD was 33.53% and 29.93% after 18 h, respectively, in continuous with the slow stirring system. TDS removal was achieved 31.44% after 24 h using the batch system. The results of these three systems were compared with each other using a one‐way analysis of variance (ANOVA). There was no significant difference between them. Azolla filiculoides is an abundant plant in northern nature that a biosystem was used for optimum usage. It can be used as an efficient, inexpensive, and affordable bioadsorbent for dairy wastewater treatment. Practitioner points: Live Azolla filiculoides was used to remove pollutants. P, Na, BOD, COD, and TDS were removed from dairy wastewater. Batch, continuous, and continuous with the slow stirring systems were used. Live Azolla was an efficient, inexpensive, and affordable bio‐adsorbent for dairy wastewater treatment. Abstract : The effect of using live Azolla filiculoides, in batch, continuous and continuous systems with low stirring was investigated to remove phosphorus, sodium, chemical oxygen demand, biological oxygen demand, and total dissolved solids in dairy effluents.